2017
DOI: 10.1002/jcpy.1005
|View full text |Cite
|
Sign up to set email alerts
|

The Name Game: How Naming Products Increases Psychological Ownership and Subsequent Consumer Evaluations

Abstract: Naming products is quite prevalent in American culture; however, we are not aware of any consumer research that explores the effects of this phenomenon. Across three studies, we demonstrate that when consumers name products, their evaluations of those products increase (e.g., attitudes, purchase intentions, and willingness to accept). We find that name fit and creativity as well as subsequent psychological ownership drive this effect. We also demonstrate that the naming effect is quite robust-replicating acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…The lake where we conducted this study is 217 square miles with a maximum depth of 83 feet. We manipulated psychological ownership of the lake by asking (vs. not asking) kayak renters to think of and write down a nickname for the lake (Stoner, Loken, and Blank 2018). A pretest with 99 Amazon Mechanical Turk (MTurk) participants confirmed that kayakers who give a lake a nickname feel greater ownership than those who do not name a lake (M name = 4.44 vs. M no name = 3.68; F(1, 97) = 4.29, p = .041; for details, see Web Appendix W1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lake where we conducted this study is 217 square miles with a maximum depth of 83 feet. We manipulated psychological ownership of the lake by asking (vs. not asking) kayak renters to think of and write down a nickname for the lake (Stoner, Loken, and Blank 2018). A pretest with 99 Amazon Mechanical Turk (MTurk) participants confirmed that kayakers who give a lake a nickname feel greater ownership than those who do not name a lake (M name = 4.44 vs. M no name = 3.68; F(1, 97) = 4.29, p = .041; for details, see Web Appendix W1).…”
Section: Methodsmentioning
confidence: 99%
“…Psychological ownership has often been studied in the context of products that are possessed or consumed by a single consumer at a time, such as a sweater (Spears and Yazdanparast 2014), a mug (Peck and Shu 2009), or a blanket (Peck, Barger, and Webb 2013). Researchers have elicited psychological ownership by, for example, having consumers name (Stoner, Loken, and Blank 2018), vote for (Fuchs, Prandelli, and Scheier 2010), or design (Kirk, Peck, and Swain 2018) a product. These manipulations take root in antecedents to psychological ownership: investing the self into the target, controlling the target, and coming to intimately know the target (Pierce, Kostova, and Dirks 2003).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…While prior studies of psychological ownership have largely addressed material possessions (e.g., Peck, Barger, and Webb 2013; Stoner, Loken, and Blank 2018), more recently researchers have explored intangible entities such as services and digital goods as potential targets of psychological ownership (Peck and Shu 2018). Mifsud, Cases, and N’goala (2015) conceptually specify service appropriation as “a process by which customers make the service their own” (p. 719) and develop possessive feelings, over time and through their investment of personal resources.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Psychological ownership theory, which began with employee attitudes and behaviors in an organization, has recently been extended to various fields such as psychology, business, consumerism, marketing, and even information systems [3,[20][21][22][23]. However, psychological ownership is typically limited to a single target.…”
Section: Psychological Ownership In the Online Contextmentioning
confidence: 99%